Closing the Gap of Justice: Providing Protection for Native American Women Through the Special Domestic Violence Criminal Jurisdiction Provision of VAWA - Singh, Shefali (Columbia Journal of Gender and Law, 2014)
Soon after Native American Diane Millich and her non-Indian husband got married, they moved into her home, located on the Southern Ute Indian reservation where she grew up. Millich’s husband began routinely abusing her, and within a year she suffered “more than 100 incidents of being slapped, kicked, punched and living in terror[.]” Millich made numerous attempts to call her local tribal and county police for help during these episodes of violence. In fact after one instance of beating his wife, Millich’s husband himself called the sheriff to report what he had done. Because he knew that there was nothing the sheriff could do. That no help would come. That he would never be prosecuted for what he did. Why? Because Millich was a Native American, Millich’s husband was not, and he was abusing her on tribal land. And because of these circumstances, as Millich later observed, “The law couldn’t touch him.” Unfortunately Millich’s circumstance is not an isolated oversight of the law. Many Indian women have not been able to seek help or justice because they happened to be trapped in this scenario: an Indian victim of a non-Indian abuser on tribal land. A recent amendment to the Violence Against Women Act (VAWA), however, was passed to change all this.